Hybrid light‐emitting devices for the straightforward readout of chiral information. Issue 12 (7th October 2021) - Salinas, Gerardo; Arnaboldi, Serena; Bonetti, Giorgia; Cirilli, Roberto; Benincori, Tiziana; Kuhn, Alexander
Abstract: Bipolar electrochemistry has gained increasing attention in recent years as an attractive transduction concept in analytical chemistry in general and, more specifically, in the frame of chiral recognition. Herein, we use this concept of wireless electrochemistry, based on the combination of the enantioselective oxidation of a chiral probe with the emission of light from a light‐emitting diode (LED), as an alternative for an easy and straightforward readout of the presence of chiral molecules in solution. A hybrid polymer‐microelectronic device was designed, using an inherently chiral oligomer, that is, oligo‐(3, 3′‐dibenzothiophene) and a polypyrrole strip as the anode and cathode of a miniaturized LED. The wireless induced redox reactions trigger light emission when the probe with the right chirality is present in solution, whereas no light emission is observed for the opposite enantiomer. The average light intensity shows a linear correlation with the analyte concentration, and the concept opens the possibility to quantify the enantiomeric excess in mixtures of the molecular antipodes. Abstract : Electrochemical chiral recognition is transduced in a wireless way into enantioselective light emission from a Light Emitting Diode.